The Influence of TikTok User-Generated Content on Destination Image and Visit Intention: Evidence from Whale Shark Tourism in Sumbawa - Sarifahtullah Sarifahtullah; Agus Santoso (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2026)
This study examines the influence of TikTok User-Generated Content (UGC) on destination image and visitation intentions for whale shark tourism in Sumbawa, with destination image as the mediating variable. Based on the Stimulus–Organism–Response (S-O-R) theory, this study investigates how TikTok tourism content influences tourists’ perceptions and behavioral intentions. A quantitative explanatory approach was used in this study. Data were collected via an online questionnaire from 100 active TikTok users who had viewed Sumbawa Whale Shark content. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that TikTok UGC has a positive and significant influence on destination image and visit intention. Destination image also positively and significantly influences visit intention and acts as a mediator in the relationship between UGC and visit intention. These results indicate that authentic and visually appealing tourism content on TikTok can effectively shape positive perceptions of the destination and drive visitation intent. This study further confirms the relevance of the S-O-R framework in explaining digital tourist behavior. This research contributes to the tourism marketing literature by expanding the application of TikTok-based UGC in shaping destination image and tourist behavioral intent, particularly among Generation Z travelers